2019
DOI: 10.1038/s41586-019-1818-7
|View full text |Cite
|
Sign up to set email alerts
|

Highly structured slow solar wind emerging from an equatorial coronal hole

Abstract: and telling us what having access to this work means to you and why it's important to you. Thank you.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
391
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 516 publications
(435 citation statements)
references
References 52 publications
26
391
0
1
Order By: Relevance
“…These findings lead us to conclude that the strahl carries the information about the coronal electron temperature at the point of its origin and can be used as a good proxy for the connectivity studies involving remote sensing and in-situ data. In fact, the origins of the solar wind measured by PSP anticipated from the strahl temperature measurements compare very well to the ones obtained using a PFSS model presented by Bale et al (2019); Badman et al (2019). Even though the measured values of T s agree very well with the coronal electron temperatures measured with the spectroscopes on-board SOHO spacecraft (David et al 1998;Cranmer 2002), we believe further analysis is required to confirm that T s is a direct measure of the electron temperature in corona.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These findings lead us to conclude that the strahl carries the information about the coronal electron temperature at the point of its origin and can be used as a good proxy for the connectivity studies involving remote sensing and in-situ data. In fact, the origins of the solar wind measured by PSP anticipated from the strahl temperature measurements compare very well to the ones obtained using a PFSS model presented by Bale et al (2019); Badman et al (2019). Even though the measured values of T s agree very well with the coronal electron temperatures measured with the spectroscopes on-board SOHO spacecraft (David et al 1998;Cranmer 2002), we believe further analysis is required to confirm that T s is a direct measure of the electron temperature in corona.…”
Section: Discussionsupporting
confidence: 80%
“…Bi-directional strahls have been observed and related to magnetic field structures like closed magnetic loops and magnetic clouds (Gosling et al 1987). Sunward directed strahls have also been observed and serve as the indicators of magnetic field structures sometimes referred to as the switchbacks (Balogh et al 1999;Yamauchi et al 2004;MacNeil et al 2017), which are frequently observed also during the first perihelion of the PSP Bale et al 2019). In this study we do not consider special cases and focus on the anti- sunward moving strahl electrons in the nominal solar wind.…”
Section: Parker Solar Probementioning
confidence: 99%
“…4(a). These magnetic field reversals, also known as "switchbacks", have been observed to be pervasive in PSP's initial orbits, but their origin and physical nature remains a mystery Bale et al 2019;Tenerani et al 2020;de Wit et al 2020;Horbury et al 2020). Directly before this 30 minute-duration switchback, Fig.…”
Section: Event 2: April Foolsmentioning
confidence: 98%
“…A highly variable streamer belt must exist to explain the small-scale magnetic and density variations in slow wind measured by PSP (e.g. Bale et al 2019), and other spacecraft further from the Sun. Coronal tomography cannot directly show such fine spatial and temporal scales.…”
Section: Summary and Future Workmentioning
confidence: 99%